2019
DOI: 10.2147/ppa.s209346
|View full text |Cite
|
Sign up to set email alerts
|

<p>How Much Information and Participation Do Patients with Inflammatory Rheumatic Diseases Prefer in Interaction with Physicians? Results of a Participatory Research Project</p>

Abstract: ObjectivePatient preferences for information and participation in medical decision-making are important prerequisites to realize a shared decision between patients and physicians. This paper aims at exploring these preferences in German patients with inflammatory rheumatic diseases and at identifying relevant determinants of these preferences.MethodsIn a cross-sectional survey, adult patients with rheumatoid arthritis (RA), spondyloarthritis (SA) or different connective tissue diseases (CTS) filled out a quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
(67 reference statements)
2
5
0
Order By: Relevance
“…27 The level of information patients need to cope and manage side effects varies widely across individuals. 28 The high prevalence of patients perceiving conflicting information is consistent with the findings from previously published studies. 13 16 21 23 29 While other studies evaluated conflicting information encountered by patients suffering from specific chronic diseases such as arthritis 7 22 or atrial fibrillation, 30 our study describes the perception of conflicting information of patients with various long-term diseases and treatments, most of them included in the primary care context, that is, community pharmacies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…27 The level of information patients need to cope and manage side effects varies widely across individuals. 28 The high prevalence of patients perceiving conflicting information is consistent with the findings from previously published studies. 13 16 21 23 29 While other studies evaluated conflicting information encountered by patients suffering from specific chronic diseases such as arthritis 7 22 or atrial fibrillation, 30 our study describes the perception of conflicting information of patients with various long-term diseases and treatments, most of them included in the primary care context, that is, community pharmacies.…”
Section: Discussionsupporting
confidence: 90%
“… 27 The level of information patients need to cope and manage side effects varies widely across individuals. 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 In previous research, multiple regressions were mainly used to analyse factors influencing participation preferences and explained between 3% and 21% of the variance. [66][67][68] While our mediation path model explained a substantial amount of variance and, more importantly, uncovered the mediating effects of attitudes and beliefs,…”
Section: Discussionmentioning
confidence: 84%
“…Models for shared decision‐making focus on the need to offer choices, discuss options, and finally come to a decision by taking into account patient understanding and preferences (6,17). In rheumatology, patients prefer different levels of involvement, ranging from predominantly doctor led to patient led (17,19,25). We found that the preference for the level of involvement is not static.…”
Section: Discussionmentioning
confidence: 99%